Kink effect in ultrathin FDSOI MOSFETs. (May 2018) - Park, H.J.; Bawedin, M.; Choi, H.G.; Cristoloveanu, S.
Abstract: Systematic experiments demonstrate the presence of the kink effect even in FDSOI MOSFETs. The back-gate bias controls the kink effect via the formation of a back accumulation channel. The kink is more or less pronounced according to the film thickness and channel length. However, in ultrathin (<10 nm) and/or very short transistors (L < 50 nm), the kink is totally absent as a consequence of super-coupling effect. For the first time, thanks to the availability of body contacts, the body potential is probed to evidence the impact of majority carrier accumulation and drain pulse duration on the kink effect onset.